The Supported Diagonal Flexion Kangaroo Position Supports Physiological Stability in Premature Infants Through a Randomized Controlled Trial - Sugiarti, Sugiarti; Sunarsih, Sunarsih; Rustina, Yeni; Efendi, Defi (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Physiological parameters are vital indicators of neonatal health, particularly in premature and low birth weight (LBW) infants. Specific Background: Kangaroo Mother Care (KMC) enhances neonatal outcomes, yet optimal positioning—such as the recently introduced Supported Diagonal Flexion (SDF) position—requires further validation. Knowledge Gap: Limited evidence exists on whether SDF positioning offers physiological advantages over the conventional upright kangaroo position. Aims: This study aimed to determine the effect of SDF positioning on physiological stability in premature and LBW infants during KMC. Method: A randomized crossover trial was conducted involving 31 mother-infant dyads. Each infant experienced both SDF and upright kangaroo positions in two sessions, with at least one hour per session. Physiological parameters—body temperature, heart rate, and oxygen saturation—were measured at baseline and post-intervention, analyzed using General Linear Model Repeated Measures and Mann-Whitney tests. Results: No statistically significant differences were observed across parameters: temperature (p=0.370), heart rate (p=0.956), and oxygen saturation (p=0.373). Novelty: This is among the first trials comparing SDF and upright KMC positions in a crossover design. Implications: Although physiological differences were not significant, SDF positioning demonstrated safety and maintained stability, supporting its use as an alternative in KMC practices for premature and LBW infants. Highlights: Highlights the safety and stability of SDF positioning in KMC. Uses a robust crossover design for internal control. Supports clinical application despite non-significant differences. Keywords: Kangaroo Mother Care, Supported Diagonal Flexion, Premature Infants, Physiological Stability, Randomized Crossover Trial